Interlingual errors in writing : a limited case study at a Malaysian university / Nor Ashikin Ab Manan and Puteri Rohani Megat Abdul Rahim - Ab Manan, Nor Ashikin; Megat Abdul Rahim, Puteri Rohani (Unit for Research and Intellect Application (UfoRIA), 2009)
Although there are some similarities in the syntactic structures of Malay and English, there are a lot more differences than there are similarities between the two languages. Therefore, it is expected that first language interference would be one of the sources of errors in the writings of Malay students who are learning English as a second language. In this study students' writings are analysed to see if there are any patterns which can be generalized as typical Malay students' errors. The major concern of this paper is to determine whether there are observable features of interference of L1 (Malay) on L2 (English) particularly in the syntactic structure of the students' writing samples. This paper aims to discuss the following problems: 1.) the instances where the syntactic structure in LI is used in L2, causing an error. 2.) the instances where the absence of a similar syntactic structure of L2 in L1, creates a difficulty for a learner in L2. 3.) the instances where a word is chosen based on its meaning in L1 but is out of context in a particular L2 sentence, causing an error. 4.) the instances where a sentence in L1 is directly translated into L2, causing an error.